Case Report: Tislelizumab–induced panuveitis: a report of two cases - Ding, Huan; Zhang, Shuyuan; Lin, Lin; Zhang, Kaiyan (Frontiers in Pharmacology, 2025)
BackgroundTislelizumab, an increasingly utilized immunotherapy for a range of malignancies, can induce a rare ocular immune-related adverse event resembling Vogt-Koyanagi-Harada-like syndrome (VKHLS). Management of complication requires careful balancing with ongoing systemic anti-tumor therapy.Case PresentationThis report describes two cancer patients who developed severe bilateral vision loss following Tislelizumab treatment. Multimodal ocular imaging confirmed the diagnosis of immune checkpoint inhibitors (ICIs)-associated uveitis, specifically a VKHLS. Both patients were managed with discontinuation of Tislelizumab and local corticosteroid therapy-transcutaneous periocular injection of triamcinolone acetonide (TA) and topical steroid eye drops, without systemic corticosteroids. Their uveitis resolved rapidly, with recovery of visual acuity.ConclusionPrompt Tislelizumab discontinuation combined with local corticosteroid therapy-transcutaneous periocular TA injections, and topical steroid eye drops may constitute an effective management strategy for ICIs-induced uveitis. This approach is particularly valuable for cancer patients in whom systemic corticosteroids are contraindicated or unsuitable.